2016
DOI: 10.7547/15-038
|View full text |Cite
|
Sign up to set email alerts
|

First Metatarsal Head and Medial Eminence Widths with and Without Hallux Valgus

Abstract: Background: Resection of the medial eminence in hallux valgus surgery is common. True hypertrophy of the medial eminence in hallux valgus is debated. No studies have compared metatarsal head width in patients with hallux valgus and control patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Lenz et al () investigated the relationship between the medial eminence width of the first metatarsal and the presence of hallux valgus using radiographs from 43 patients with hallux valgus and 27 patients without. They found that both the first metatarsal head and medial eminence widths were significantly greater in patients with hallux valgus on the AP view.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lenz et al () investigated the relationship between the medial eminence width of the first metatarsal and the presence of hallux valgus using radiographs from 43 patients with hallux valgus and 27 patients without. They found that both the first metatarsal head and medial eminence widths were significantly greater in patients with hallux valgus on the AP view.…”
mentioning
confidence: 99%
“…In addition, metatarsals and phalanges move to a more parallel position in relation to the radiographic image with weight bearing resulting in an apparent lengthening on the radiographic image. Lenz et al (2016) investigated the relationship between the medial eminence width of the first metatarsal and the presence of hallux valgus using radiographs from 43 patients with hallux valgus and 27 patients without. They found that both the first metatarsal head and medial eminence widths were significantly greater in patients with hallux valgus on the AP view.…”
mentioning
confidence: 99%